Geospative assessment of trade and economic cooperation of Ukraine with the countries of Europe - Zoya Boyko (Časopis Socìalʹno-Ekonomìčnoï Geografìï, 2020)
The theoretical and methodological foundations of trade and economic cooperation and their impact on the development of tourism and the service sector of the national economies of European countries are analyzed. The main factors of influence on the current state of trade and economic cooperation between Ukraine and European countries are characterized, including: the advantage of raw materials and products of a low level of processing; suspension of production in the occupied regions of Eastern Ukraine (Donetsk and Luhansk), deterioration of the conditions for attracting external financing; unstable economic and political situation, as well as depletion of international reserves. The article traces the factors of the basing of international trade, including the division of labor, provision of a favorable climate, land and labor force, provision of a high level of technology. The classification signs of trade and economic relations are presented: in terms of dynamics, structure, location, level of development of partner countries for trade. The factors of influence on the state of trade and economic cooperation and services of the national economies of the studied countries are given. The leading trade partners of Europe for Ukraine, their main commodity and raw materials exchange are analyzed. It was revealed that ferrous metals, electric machines, fats and oils of both animal and vegetable origin, nuclear fuel, boilers, machines, grain crops, ores, slags and ash dominate among Ukrainian merchandise exports. Among the services dominated by trans-portation services, services for the processing of material resources, services in the field of telecommunications, computer and infor-mation, business services, repair and maintenance services. Imports are dominated by mineral fuel, boilers and equipment for the electric power industry, products of other engineering enterprises, chemical products, etc. The regions of Ukraine were divided into groups according to the level of exports of goods and services to European countries, according to which Kherson and Chernivtsi regions have the lowest indicators European exports, 16 regions of Ukraine belong to the average export level.